Metode Craft Berbantuan Perangkat Lunak WinQsb Untuk Usulan Perbaikan Tata Letak Fasilitas V2.0 Pada Industri Dompet CV. X - Wahyuni, Rossi Septy; Safitri, Astri Anggraini (Jurnal Ilmiah Teknologi dan Rekayasa, 2014)
Facility layout design is the main foundation in a production and work area layout system employing the width to place machines or other supporting production facilities and to make it easier for moving materials in order to achieve orderly, safety, and comfortable work condition and material flow. The improvement proposal done on facility layout of wallet industry uses CRAFT method with WinQSB V2.0 software. Later, the facility layout improvement will change some area of the facility in accordance to the material flow, so that the distance of flowing and handling cost can be reduced. The total of handling cost of the wallet industry’s facility layout before the improvement is amounted to IDR 785.000,-. Meanwhile, the total of handling cost in the improvement proposal is amounted to IDR 563.100,-. Based on the result of handling cost before and after the improvement, the percentage difference is 28,26%.Keywords: Wallet Industry, Layout Proposal, CRAFT Method